2005
DOI: 10.3354/meps302177
|View full text |Cite
|
Sign up to set email alerts
|

Spatially heterogeneous, synchronous settlement of Chthamalus spp. larvae in northern Baja California

Abstract: We evaluated the spatial variability in barnacle settlement at scales of 10s to 100s of meters (among-sites: 300 m; within-site: 30 m) along 1 km of coastline in the Bay of Todos Santos, northern Baja California, Mexico. Settlement of the intertidal barnacles Chthamalus spp. was monitored daily from April 1 to May 10, 2002, and thereafter every other day to September 18, 2002. Concurrently, temperature of the water column was measured every 15 min, and hourly wind speed and direction data were acquired from a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
1
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 56 publications
1
28
1
3
Order By: Relevance
“…Settlement, however, clearly peaked following minimum temperatures during the spring tide as temperatures were beginning to rise. Thus, internal tides take a form that is conducive to the shoreward transport of cyprids soon after spring tides, as has been observed elsewhere along the west coast of North America (Shanks 1983, 1986, 2009, Pineda 1991, Ladah et al 2005). …”
Section: Barnacle Settlementmentioning
confidence: 94%
See 1 more Smart Citation
“…Settlement, however, clearly peaked following minimum temperatures during the spring tide as temperatures were beginning to rise. Thus, internal tides take a form that is conducive to the shoreward transport of cyprids soon after spring tides, as has been observed elsewhere along the west coast of North America (Shanks 1983, 1986, 2009, Pineda 1991, Ladah et al 2005). …”
Section: Barnacle Settlementmentioning
confidence: 94%
“…A number of studies have presented data purported to demonstrate that cyprids are transported onshore by upwelling-relaxation events, reviewed by Shanks (2009), but these studies followed recruitment at weekly or longer intervals and suffer from aliasing as well as an unknown amount of mortality between settlement and the recruitment measurement (Shanks 2009). Many studies that have measured cyprid settlement daily have, however, found significant correlations between settlement and the fortnightly tidal cycle (Shanks 1986, 2009, Pineda 1991, Pineda & Caswell 1997, Ladah et al 2005, Tapia & Navarrete 2010, suggesting that transport was due to the internal tides. These studies found weak or no evidence to support delivery of cyprids by upwelling-relaxation events, although Hawkins & Hartnoll (1982) ob served higher settlement during onshore winds.…”
Section: Phytoplankton Pulsesmentioning
confidence: 99%
“…Large, tidally generated internal waves and bores can transport larvae onshore along the 80 Pacific coast of the USA (Pineda 1994, Shanks 2002, Ladah et al 2005. Internal waves can deliver larvae to shore in warm, saline surface waters during any phase of the tidal amplitude cycle (Table 1; Rosenfeld 1990, Shanks 2002.…”
Section: Introductionmentioning
confidence: 99%
“…O deslocamento da termoclina para regiões menos profundas da coluna d'água induziria os movimentos internos das massas d'água e o transporte das larvas. Assim, a variabilidade espacial do assentamento larval registrado ao longo da costa poderia estar relacionado à variabilidade na intensidade da estratifi cação da coluna d'água, onde locais com maior estratifi cação apresentariam maior assentamento (Pineda & Lopez 2002, Ladah et al 2005. A alternância entre água fria e quente promove a formação de frentes de água quente que se movimentam em direção à costa (Pineda 1994).…”
Section: Frentes Associadas Ao Movimento De Massas D'água Mais Densa unclassified